The Genesis of the Concept of Land - Smetona, Marius; Smetonienė, Anželika (Vilnius University Open Series, 2020)
Various sources confirm that a human and the land have been connected through an exceptional link. However, an idealistic image of land has been getting weaker and a present individual has felt a changed connection with the land. The land is not the sole source of livelihood for people any more and its association with pagan rituals, deities and nature has become less and less frequent. The more formal understanding of land (earth) as a planet has prevailed in Lithuanian lexicography, whereas in other sources the land is associated only with hard work. The very concept of land is broad and complex, therefore, it is important to analyse the image that emerges at a subliminal level in the head of a Lithuanian, while he/she is thinking about the land. The whole concept LAND is analysed implementing the project “Bread. Land. Mother” financed by the State Commission of the Lithuanian Language (2018–2020). This article presents the lexicographic analysis and the data of students’ survey. The analysis of questionnaire revealed an obvious fact that the image of land is perceived by every individual in accordance with influence of the surrounding environment and the worldview constructed by an individual himself or herself. The concept is broad and every individual may have a significantly different understanding of it. Some people see it only as a physical plane, whereas others feel the link with land at a spiritual level because it is home or even more than this.
Keywords: concept; land; surveys; lexicography